2018
DOI: 10.1021/acs.analchem.7b05372
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the High-Field Orbitrap Fusion for Compound Annotation in Metabolomics

Abstract: Annotation of signals of interest represents a key point in mass spectrometry-based metabolomics studies. The first level of investigation is the elemental composition, which can be deduced from accurately measured masses and isotope patterns. However, accuracy of these two parameters remains to be evaluated on last generation mass spectrometers to determine the level of confidence that can be used during the annotation process. In this context, we evaluated the performance of the Orbitrap Fusion mass spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 32 publications
5
20
0
Order By: Relevance
“…In this context, a set of 47 standard molecules was first used to develop and optimize DDA and DIA (SWATH) acquisition methods, involving either or both non-resonant higher energy collision-induced dissociation (HCD), or ion trap resonant collision-induced dissociation (CID) conditions. The 47 chemicals comprising this test set were those already used in a previous study [6] and well ionized in ESI+ mode while exhibiting large chemical, mass and retention time diversity when analyzed on a C 18 column (Supplementary Material, Table S1). As we observed in a previous study [29], such a C 18 column is not the most suited one to separate metabolite isomers, but is the most demanding in terms of MS-MS/MS acquisition speed (due to the narrow chromatographic peaks).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this context, a set of 47 standard molecules was first used to develop and optimize DDA and DIA (SWATH) acquisition methods, involving either or both non-resonant higher energy collision-induced dissociation (HCD), or ion trap resonant collision-induced dissociation (CID) conditions. The 47 chemicals comprising this test set were those already used in a previous study [6] and well ionized in ESI+ mode while exhibiting large chemical, mass and retention time diversity when analyzed on a C 18 column (Supplementary Material, Table S1). As we observed in a previous study [29], such a C 18 column is not the most suited one to separate metabolite isomers, but is the most demanding in terms of MS-MS/MS acquisition speed (due to the narrow chromatographic peaks).…”
Section: Resultsmentioning
confidence: 99%
“…We also observed that complex and composite DIA-MS/MS spectra can be efficiently exploited to identify metabolites in plasma thanks to a reference tandem spectral library made from authentic standards while also providing a valuable data resource for further identification of unknown metabolites. Finally, we found that adding multi-event MS/MS acquisition did not degrade the ability to use survey MS scans from DDA and DIA workflows for the reliable absolute quantification of metabolites down to 0.05 ng/mL in human plasma.Metabolites 2020, 10, 158 2 of 17 and thus, metabolite annotation and identification still represent major bottlenecks in untargeted metabolomics [3,4].The successful identification of metabolites requires a combination of information lines exploited in conjunction, including accurate LC retention time, high mass measurement accuracy (<1 ppm), isotope pattern and isotope fine structure measurement as well as high-quality fragmentation spectra [5,6]. High mass resolution (>100,000) allows for the measurement of isotope pattern and isotope fine structure (through the distinction of isobaric isotopes), which is particularly useful for confident compound annotation [6].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Two categories of isotopologues may be distinguished: (a) the endogenous ones, ie, species that exist due to the natural occurrence of different isotopes for a chemical element (such as carbon‐13, nitrogen‐15, or sulfur‐34 that are natural isotopes of their most common counterpart carbon‐12, nitrogen‐14, and sulfur‐32, with relative abundance of 1.11%, 0.38%, and 4.40%, respectively); (b) the isotopically labelled ones, ie, species isotopically enriched with less abundant naturally occurring isotopes (eg, carbon‐13, hydrogen‐2, or nitrogen‐15) and synthetically produced either via biological or chemical processes. Endogenous isotopologues. Today, high‐resolution mass spectrometry and especially the new Orbitrap instrument generation (reaching a resolution of 500 000 at m/z 200) can allow distinguishing between isobaric isotopologue ions co‐occurring in the natural isotope pattern of a given metabolite, which can be really helpful for an accurate metabolite annotation . For instance, the isobaric 15 N 1 ‐ and 13 C 1 ‐isotopologues of the same molecule might be potentially resolved thanks to HRMS.…”
Section: Illustrative Examples and Discussionmentioning
confidence: 99%